CHOOSING NOT TO CHOOSE IS A CHOICE: A NOBLE LESSON OF THE BADUY PEOPLE IN INTERPRETING NEUTRAL CHOICES IN VOTING IN GENERAL ELECTIONS - Lestari, Ratih (UI Scholars Hub, 2023)
Democracy can simply be interpreted as